"A spirit of strange meaning": The Chinese Roots of Wordsworth's Monism in The Ruined Cottage. Issue 2 (17th February 2023) - Liu, Yu
ABSTRACT: In both his life and poetry, The Ruined Cottage marked a decisive breakthrough for Wordsworth, which resulted from his daring adoption and sustained use of a monistic idea. Though hitherto mostly dismissed or construed as a derivative of Platonism, Stoicism, Christian mysticism, and/or other conventional English and European concepts and usually seen as part of his supposedly quietist retreat from radical politics, the philosophy of One Life which Wordsworth promoted was in reality a recognizably unconventional conceptual innovation, which indeed made possible his poetic and political innovations in The Ruined Cottage and beyond. In the larger context of ideas that extends well beyond England and Europe and involves in particular the Chinese cosmological belief in tianren heyi or humanity's unity with heaven, this essay explores Wordsworth's innovative use of monism in The Ruined Cottage and argues for a significantly different understanding of Wordsworth and the related rise of English Romanticism.